2004
DOI: 10.1002/ijc.20285
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic activity of the photodynamic agent hypericin in the dark

Abstract: A unique property of the photodynamic signal transduction inhibitor hypericin (HY) is high functionality in the dark, which has been shown to result in portfolio of anticancer activities both in vitro and in vivo. Here we show that treatment with HY significantly reduces growth rate of metastases in 2 murine models: breast adenocarcinoma (DA3) and squamous cell carcinoma (SQ2 Cancer is currently viewed as a cell cycle disease. Strategies to treat malignancies are thus shifting from toxic chemotherapy to agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 23 publications
3
47
0
Order By: Relevance
“…These studies revealed impressive anticancer effects regarding tumor growth and anti-angiogenic effects (16,18). Interestingly, hypericin had also anti-metastatic and anti-angiogenic effects in the dark (19,20). Rhabdomyosarcoma is associated with poor survival in advanced tumor stages.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed impressive anticancer effects regarding tumor growth and anti-angiogenic effects (16,18). Interestingly, hypericin had also anti-metastatic and anti-angiogenic effects in the dark (19,20). Rhabdomyosarcoma is associated with poor survival in advanced tumor stages.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Plk1 contains a destruction box-like motif and is a substrate of the anaphase-promoting complex/cyclosome, a cell cycleregulated ubiquitin ligase (Kotani et al, 1999;Lindon and Pines, 2004). Intracellular Plk1 levels also appear to be controlled by the molecular chaperone Hsp90, since Plk1 expression levels decrease when cells are treated with compounds that disrupt Plk1:Hsp90 binding (Simizu and Osada, 2000;Blank et al, 2003).…”
Section: Cells In Culturementioning
confidence: 99%
“…Because BALB/c mice bearing SQ2 tumors die primarily from lung metastases, 28 the major increase in life expectancy induced by the combination of 224 Ra-loaded wires and CP indicated that inhibition of the metastatic process may be involved. Thus, we examined the metastatic burden in the lungs from untreated and treated mice and observed that the 224 Ra wires þ CP treatment group attained a significant reduction of 51% in the lung metastatic load compared with the group of inert-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…The SQ2 cell line 28 was kindly provided by Dr. Gad Lavie from the Sheba Medical Center, Tel-Hashomer, Israel. This is a murine anaplastic cell line and was generated from an SCC tumor that developed spontaneously in a male BALB/c mouse.…”
Section: Tumorsmentioning
confidence: 99%